Development of a procedure for the structural design of roller coaster structures: The supporting structures. (1st August 2018) - Braccesi, C.; Cianetti, F.
Highlights: We developed a design procedure for Roller Coaster supporting structures. The stiffness matrix betweenconnection points and rail and supporting structures is obtained. The procedure was validated on an industrial test case. Abstract: In this paper a procedure for the design of the structures of a generic roller coaster ( RC ) is described. This activity is part of a partnership that the authors are entertaining with one of the major European amusement park industries. The full procedure, developed on theoretical bases and under simplified hypotheses, aims to make designers able to properly and quickly size the complete structure (for complete structure authors mean rails and support structures). In the present paper the design of the support structures is presented. The data, needed by this procedure, are: the rail track tridimensional geometry and the time histories of contact forces between vehicles and rails. The procedure has been subsequently verified by applying it to an existing RC in order to test all its capabilities and foresee future development and improvement, aiming to insert it in a consolidated general procedure, ever growing and expanding.